Enhancing methane production from anaerobic co‐digestion of cow manure and barley: Link between process parameters and microbial community dynamics. Issue 1 (5th July 2019) - Ince, Orhan; Akyol, Çağrı; Ozbayram, Emine Gözde; Tutal, Bilgesu; Ince, Bahar
Abstract: The effects of selected process parameters (i.e., temperature, inoculum to substrate ratio [I:S], and inoculum source) on methane production and microbial community structure were investigated in lignocellulose‐based anaerobic digestion tests. The results highlighted that dynamic response of microbial communities in changing process parameters subsequently affected anaerobic digestion performance. Co‐inoculation of cow rumen fluid to the seed sludge improved the methane yield by 18%. The overall highest methane yield (278 mL CH4 /g volatile solids) was obtained when cow rumen fluid was co‐inoculated with anaerobic seed sludge with an I:S ratio of 1:2 at mesophilic temperature. Based on 16S rRNA gene amplicon sequencing results, Clostridium, Bacteroides, and Bacillus were the predominant bacterial genera in all anaerobic digesters. The highest relative abundances of Clostridum and Bacillus were detected in the thermophilic anaerobic digester. The relative abundance of Rikenella ; known for high cellulolytic activity, was significantly higher only in the cow rumen fluid‐added digester. Comparatively higher abundances of these lignocellulose‐degraders synergistically affected volatile fatty acids as well as methane production in these anaerobic digestion set ups. Methanobacterium was the most abundant methanogen in the digesters inoculated only with anaerobic seed sludge; whereas, Methanobrevibacter dominated the digester that was co‐inoculated with cow rumen fluid.